Do pollution and climate influence respiratory tract infections in children? - Passos,Saulo Duarte (2014)
To review if pollution and climate changes can influence respiratory tract infections in children. Data source: articles published on the subject in PubMed, SciELO, Bireme, EBSCO and UpTodate were reviewed. The following inclusion criteria were considered: scientific papers between 2002 and 2012, study design, the pediatric population, reference documents such as the CETESB and World Health Organization Summary of the data: We analyzed research that correlated respiratory viruses and climate and/or pollution changes. Respiratory syncytial virus has been the virus related most to changes in climate and humidity. Other "old and new" respiratory viruses such as Human Bocavirus, Metapneumovirus, Parechovirus and Parainfuenza would need to be investigated owing to their clinical importance. Although much has been studied with regard to the relationship between climate change and public health, specific studies about its influence on children's health remain scarce.